Consumer Representative Actions in the Financial Sector - Wijayanti, Sita Adelia Jatu; Cahyono, Akhmad Budi (Faculty of Law, Andalas University, 2023)
The presence of a non-governmental consumer protection organization plays a vital role in assisting consumers whose position tends to be weak and overseeing the implementation of bank executions so that they are carried out fairly. The organization can also represent a broad group of consumers to appear before the court for consumer protection. This study analyzes the legal protection of consumers based on the omnibus financial law of the Financial Sector Development and Strengthening Law and the Consumer Protection Law as well as the role of non-governmental consumer protection institutions in providing advocacy and consultation to consumers in the financial services sector. This study also addresses the legal standing of nongovernmental consumer protection organizations in court. This study aims to provide an analysis of consumer protection in the financial services sector and the role of nongovernmental consumer protection organizations in their involvement in consumer disputes in the financial services sector. The results of the research are based on case studies, that there are still lawsuits filed by non-governmental consumer protection organizations on behalf of consumers in the financial services sector that do not meet the requirements as stipulated in the Law.